Heptabladed β-propeller lectins PLL2 and PHL from Photorhabdus spp. recognize O-methylated sugars and influence the host immune system - Fujdiarová, Eva; Houser, Josef; Dobeš, Pavel; Paulíková, Gita; Kondakov, Nikolay; Kononov, Leonid; Hyršl, Pavel; Wimmerová, Michaela (The FEBS journal, 2021)
O-methylation is an unusual sugar modification with a function that is not fully understood. Given its occurrence and recognition by lectins involved in the immune response, methylated sugars were proposed to represent a conserved pathogen-associated molecular pattern. We describe the interaction of O-methylated saccharides with two β-propeller lectins, the newly described PLL2 from the entomopathogenic bacterium Photorhabdus laumondii, and its homologue PHL from the related human pathogen Photorhabdus asymbiotica. The crystal structures of PLL2 and PHL revealed up to 10 out of 14 potential binding sites per protein subunit to be occupied with O-methylated structures. The avidity effect strengthens the interaction by 4 orders of magnitude. PLL2 and PHL also interfere with the early immune response by modulating the production of reactive oxygen species and phenoloxidase activity. Since bacteria from Photorhabdus spp. have a complex life cycle involving pathogenicity towards different hosts, the involvement of PLL2 and PHL might contribute to the pathogen overcoming insect and human immune system defences in the early stages of infection. DATABASES: Structural data are available in PDB database under the accession numbers 6RG2, 6RGG, 6RFZ, 6RG1, 6RGU, 6RGW, 6RGJ, and 6RGR.
Keywords: metylace; hemolymfa; Animals; imunitní systém; můry; Gram-Negative Bacterial Infections; Hemocytes; Immune System; hemocyty; bakteriální proteiny; Lectins; Bacterial Proteins; lidé; cukry; gramnegativní bakteriální infekce; Moths; Immunity; Hemolymph; imunita; lektiny; Methylation; Photorhabdus; interakce hostitele a patogenu; Sugars; zvířata; Host-Pathogen Interactions; Humans